PRAKRITI ANALYSIS AND ITS CLINICAL SIGNIFICANCE - Ahmad Wani, *Bilal; Kumar Mandal, Sisir; Godatwar, Pawankumar (International Journal of Ayurveda and Pharma Research, 2017)
Prakriti is defined as the state of an individual in its natural form. Ayurveda classifies people on the basis of Prakriti as every person is supposed to have a fixed Prakriti that is formulated by the condition of Tridosha at the time of union of sperm and ovum inside the uterus. Predominance of any one, two, or all the three Dosha (body humors- Vata, Pitta and Kapha) determines the Prakriti of an individual. So Prakriti refers to genetically determined anatomical, physiological and psychological constitution of an individual. Prakriti also determines the response of an individual to environmental factors, drugs and susceptibility to diseases making it one of the earliest known concepts of preventive and personalized or genomic medicine. Opposite to the Prakriti is Vikriti which means diseased state of an individual. Until the normal is not known, abnormality cannot be found, so Prakriti plays an important role in determining Vikriti. Acharya Charaka has mentioned Dashavidha Pariksha in which Prakriti analysis is done first and Vikriti analysis next to understand the nature and severity of disease, reaction of body to the drugs (pharmacogenomics), selection of drugs and their doses, prognosis of the disease and preventive measures such as diet, diurnal and seasonal regimes. So Prakriti emphasizes on the individuality and plays an important role in diagnosis, preventive medicine, and therapeutics.